Cognitive Dysfunction in Repeat Expansion Diseases: A Review - Zhang, Sizhe; Shen, Lu; Jiao, Bin (Frontiers in Aging Neuroscience, 2022)
With the development of sequencing technique, more than 40 repeat expansion diseases were identified during the past 2 decades. Moreover, the clinical features of these diseases show some commonality, and the nervous system, especially cognitive function was affected in part of these diseases. However, the specific cognitive domains impaired in different diseases were inconsistent. Here we survey the literature on the cognitive consequences of the following disorders presenting cognitive dysfunction, and summarized the pathogenic genes, epidemiology, and different domains affected in these diseases. We found that the cognitive domains affected in neuronal intranuclear inclusion disease were widespread including executive function, memory, information processing speed, attention, visuospatial function and language; C9ORF72-frontotemporal dementia patients showed impairment in executive function, memory, language and visuospatial function. While in Huntington's disease, executive function, memory and information processing speed were affected. As for fragile X-associated tremor/ataxia syndrome, executive function, memory, information processing speed and attention were impaired. Moreover, spinocerebellar ataxias showed abroad damage in almost all the cognitive domains except for the relatively intact language ability. Some other diseases with relatively rare clinical data also indicated cognitive dysfunction, such as myotonic dystrophy type 1, progressive myoclonus epilepsy, Friedreich ataxia, Huntington Disease like 2 and cerebellar ataxia, neuropathy, vestibular areflexia syndrome. We drew a cognitive function landscape of the relating repeat expansion diseases and may provide an aspect for differential diagnosis through cognitive domains.